(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
Type 2 diabetes mellitus is one of the most leading causes of death and disability worldwide among the lifestyle disorders where dietary and lifestyle factors play a major role. Prameha is a classical metabolic disorder of tissue and cellular level. Unhealthy diet and physical inactivity are the leading causes of the lifestyle disorders; Prameha is also among them as mentioned by Acharya Charaka. A survey study was carried out to study the prevalence of Prameha patients and associated risk factors in the light of epidemiological aspect. 120 diabetic patients from OPD of Institute of Post Graduate Ayurvedic Education and Research, Kolkata, were selected randomly according to their registered address as residents of Kolkata. A survey proforma along with consent form was prepared and detailed history of each patient fulfilling the subjective criteria of Prameha and objective criteria of Diabetes Mellitus were taken. On considering data of Santarpana nidana, maximum patients were taking excess carbohydrate (90%); dairy products (82.5%); fried and fatty diet (68.33%); sweets and sugarcane preparations (79.16%); junk and fast foods (82.5%) in excessive quantity and 51.66% patient were found to be with increased BMI. Factors observed related to lifestyle are Divaswapna (60%) and Asyasukham (65%). Udvega (stress) were found in 88.33% of patients. This study revealed that prevalence of carbohydrate rich diet; dairy products; junk food and increased BMI are found dominant in diabetes patients in Kolkata. Avoidance of these faulty dietary habits and sedentary lifestyle, further progression of the diabetes along with its complications can be inhibited.